Advancing and Translating Knowledge in Vascular Medicine - Husmann, Marc; Barton, Matthias (Frontiers in Cardiovascular Medicine, 2014)
For centuries, physicians have depended on the use of written information to gain knowledge. Book printing and binding introduced by Gutenberg in the fifteenth century revolutionized and accelerated the distribution of information. Advancing medical knowledge and progress is not only linked to the scientific quality of a discovery determining it will be accepted by the peers but also by its communication and sharing of new findings with the medical community. All these factors determine whether new knowledge will advance and improve clinical practice, medical education, and ultimately, patient care, and human health. In the past decade medical publishing has witnessed a revolution with regard to the instant, online availability of published “open access” information, which can be accessed and printed from any computer connected to the internet. As an example, how language and availability of printed information may affect distribution of knowledge, we discuss the publication of the first results of balloon angioplasty in patients with peripheral vascular disease 40 years ago by Andreas Grüntzig, M.D. at the University of Zürich. Vascular Medicine, as part of Frontiers in Cardiovascular Medicine, will provide open access provided to all published content for sharing and distributing new and most up-to-date information on clinical practice and medical knowledge in vascular medicine. We anticipate that the ongoing transformation of scientific publishing through open access will further accelerate this process and make new knowledge available even faster. Immediate, unrestricted, and rapid access to the most current knowledge published will play a role in maintaining and advancing human vascular health across the globe.